2021
DOI: 10.1021/acsami.1c16269
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Drug-Releasing Supramolecular Hydrogel for Preventing Postoperative Peritoneal Adhesion

Abstract: Hydrogels have attracted widespread attention for breaking the bottlenecks faced during facile drug delivery. To date, the preparation of jelly carriers for hydrophobic drugs remains challenging. In this study, by evaporating ethanol to drive the formation of hydrogen bonds, hydrophilic poly(vinyl alcohol) (PVA) and certain hydrophobic compounds [luteolin (LUT), quercetin (QUE), and myricetin (MYR)] were rapidly prepared into supramolecular hydrogel within 10 min. The gelation performance of these three hydrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 71 publications
1
9
0
Order By: Relevance
“…It is generally accepted that this is the source of adhesive strength. , Based on the investigations in our previous study, , we decided to model epoxy resin using the fragment model shown in Figure b, which is a simplified version of the epoxy resin structure (Figure a). Hereafter, this model will be referred to as the “epoxy molecule.” It should be noted that molecular simulations of interfaces using monomers and oligomers instead of polymers are widely accepted in various fields, and findings that are qualitatively consistent with experimental results can be obtained from them. , The modeling of omitting the epoxy group is reasonable because the epoxy ring opens during the formation of the three-dimensional cross-linked polymer chain to become a hydrocarbon chain with a hydroxyl group. , This study is the first step toward future research, including the effects of three-dimensional networks of polymer chains in epoxy resins, using a model that more closely resembles a large-scale realistic system.…”
Section: Methodssupporting
confidence: 62%
“…It is generally accepted that this is the source of adhesive strength. , Based on the investigations in our previous study, , we decided to model epoxy resin using the fragment model shown in Figure b, which is a simplified version of the epoxy resin structure (Figure a). Hereafter, this model will be referred to as the “epoxy molecule.” It should be noted that molecular simulations of interfaces using monomers and oligomers instead of polymers are widely accepted in various fields, and findings that are qualitatively consistent with experimental results can be obtained from them. , The modeling of omitting the epoxy group is reasonable because the epoxy ring opens during the formation of the three-dimensional cross-linked polymer chain to become a hydrocarbon chain with a hydroxyl group. , This study is the first step toward future research, including the effects of three-dimensional networks of polymer chains in epoxy resins, using a model that more closely resembles a large-scale realistic system.…”
Section: Methodssupporting
confidence: 62%
“…Supramolecular hydrogels based on natural polymers such as polyphenols and polysaccharides are gradually favored by workers who study postoperative antiadhesion materials due to their injectable nature, strong adhesion and self-healing functions. [279][280][281][282] The supramolecular PVA/QUE hydrogel prepared by Song et al 51 rapidly within 10 minutes provided an effective and safe anti-adhesion barrier for drug release, significantly improving the antiadhesion effect. In the study of Dong et al, 156 the supramolecular composite hydrogel was shown to completely cover the surface of irregular damaged tissues and effectively reduce the formation of postoperative adhesions by reducing the adhesion and growth of bacteria.…”
Section: Application Of Supramolecular Hydrogels In Wound Repairmentioning
confidence: 99%
“…Hydrogels have been widely used in biomedical applications, including drug delivery, soft actuators, tissue engineering, and human–machine interfaces. However, the adhesion of most hydrogels to the solid interface is weak, which is mainly affected by the bulk toughness and interface toughness. The bulk toughness can prevent hydrogel damage from high mechanical deformation, while the interfacial toughness enables tough adhesion of hydrogels to substrate surfaces. , To achieve tough hydrogel–solid interfaces, the interfaces should possess intrinsic adhesion and the hydrogels should provide high fracture toughness. The interfacial toughness of hydrogel materials can be estimated by Γ = Γ 0 + Γ D , where Γ 0 is the intrinsic adhesion arising from the chemical or/and physical interactions at the hydrogel–substrate interfaces such as chemical anchorage, hydrogen bond, mechanical interlock, etc., while Γ D is the bulk energy dissipation . The tough adhesion of hydrogels to surfaces is attained via the synergy of mechanics, chemistry, and topology. , The silane-based chemical anchoring strategy is proposed to enhance the intrinsic fracture toughness of anchoring at various solid surfaces, and the adhesion energy between them may exceed 1000 J m –2 .…”
Section: Introductionmentioning
confidence: 99%